The diagnostic utility of serum ascites albumin gradient against ascitic fluid total protein for detection of liver disease in patients of ascites- A comparative study - Kansal, Archana; Aharwar, Sandeep; Trikha, Sushma; Sharma, Ashish; Sahai, Shweta (International Journal of Medical Research and Review, 2015)
Introduction: Various studies have demonstrated superiority of SAAG (serum ascites albumin gradient) in classifying ascites compared to transudate-exudate concept but with conflicting observations. Ascitic fluid total protein (AFTP) level in ascitic fluid is a much cheaper alternative to the serum ascites albumin gradient ratio. Hence in the study, we have compared the diagnostic accuracy of the old cheaper traditional method against the new method. Methods: Total 102 patients of Ascites were included in the study from J.A. group of hospital, G.R. Medical College (M.P.) in year 2013-15. All medical causes of ascites were included in our study and Non medical causes were excluded. The collected data was analyzed by using Pearson Chi-square statistical analysis to determine correlation between variables. Result: For prediction of liver disease it was found that SAAG was significantly (p value 0.0341) more predictive of Liver disease compared to AFTP. SAAG (p value<0.0009) and AFTP (p value 0.49) were both significant for differentiating cause of ascites when comparison was done between liver and non-liver disease. Conclusion: AFTP is a good surrogate marker for detection of liver disease in ascites. AFTP is an excellent diagnostic test for detection of certain extra hepatic diseases leading to ascites like tubercular peritonitis sub-acute bacterial peritonitis and anaemia-hypo-proteinemia.